SOSIALISASI DAN EDUKASI TERKAIT SERANGAN DIGITAL - Silalahi, Sari Muthia; Sigiro, Marojahan MT; Sinambela, Eka Stephani; Wowiling, Gerry Italiano; Manalu, Istas; Simatupang, Frengki (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The socialisation of understanding digital attacks aims to help the community, especially students in the Toba area, regarding the types of digital attacks and how to deal with them. The socialisation activity was conducted in several junior high and senior high schools in Toba. Socialisation was also carried out to help the students understand the types of digital attacks by questionnaire. The contents of the questionnaire were to see how large the percentage of digital attacks, such as identity forgery, phishing, and data leaks, were experienced by students. The results of 315 respondents showed that digital attacks were in the